Comparative Analysis on Performance of Tri-sectional and Four-sectional Air Preheater in 1000MW Unit. Issue 1 (October 2020) - Xu, Chunxing
Abstract: This paper mainly compares and analyzes the characteristics and performance of air preheater for tri-sectional and four-sectional, it is found that the four-sectional air preheater has a great advantage in economy, this is mainly because the four-sectional air pre-heater has obvious advantages in reducing air leakage rate, it can reduce air leakage of air preheater, reduce power consumption of fan and improve thermal efficiency of unit significantly. In addition, it is found that the deviation range of flue gas temperature distribution of four-sectional air pre-heater is small by measuring the flue gas side temperature of the air preheater, the overall temperature of flue gas side is higher than that of acid dew point, it is more conducive to the prevention of low-temperature corrosion at the cold end of air preheater, and the operation of the unit is more safe.